(untitled) (Praxis Educativa, 2024)
This article presents part of the findings that emerge from the dissertation of the Bachelor’s Degree in Educational Sciences at the National University of Mar del Plata and that addresses the corporal and emotional availability of teachers at the Initial Level. From a hermeneutic-narrative approach that expands towards an autobiographical dimension, we seek to interpret what meanings teachers construct about bodily and affective availability from their own testimonies and how they are configured from the prescriptions, fears and pleasures in their practices. teaching. The study seeks to highlight the voices of teachers as alternative ways of knowing, thinking and feeling the world that allows us to understand it in its complexity in a framework between the normative, classroom, curricular and bonding levels.